Shariah analysis of temporary waqf vis-à-vis hibah umra and ruqba - Md. Habibur, Rahman; Noor Mohammad, Osmani (2018)
The paper intends to make a shari’ah analysis on temporary waqf vis-à-vis hibah umra and ruqba. Unlike the majority, Maliki School allows making a temporary waqf subject to a defined period of time. Umra and ruqba are the two forms of hibah in which donation is made conditional with demise of the donor and survival of the beneficiary. They are valid in shari’ah provided that the donation shall not be back to the donor in any case. This is a library based study and it has been accomplished through investigation and analysis of the relevant documents and literatures. The paper posits that umra and ruqba donations can be integrated into the temporary waqf because all of them are conditional in nature. It concludes that temporary waqf differs from hibah umra and ruqba as the endowment can be back to the donor after expiry of the duration or demise of the beneficiary while umra and ruqba donations cannot be back to the donor after demise of the beneficiary. They shall go to the inheritor(s) of the beneficiary instead.